Vector of the Intelligent Office Buildings Formation - Golub, Kristina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Every day the architecture expands its borders and opportunities. In meeting the challenges of commercial office buildings designing, which include not only the aesthetic and functional aspects, the efficiency problem of their exploitation becomes more actual, including resource conservation, energy efficiency, environmental friendliness, environmental protection, safety (the fire, terrorism, natural disaster, etc.), comfortable working conditions, reduced operating expenses and economy.
Keywords: intelligent building; building management systems; office building; functional; artificial intelligence; secure architecture; inteligentny budynek; system zarządzania budynkiem; budynek biurowy; funkcjonalność; sztuczna inteligencja; bezpieczna architektura